Approaching the standard quantum limit of mechanical torque sensing - P. H. Kim (Nature Portfolio, 2016)
Cavity optomechanics enables measurement of torque at levels unattainable by previous techniques, but the main obstacle to improved sensitivity is thermal noise. Here the authors present cryogenic measurement of a cavity-optomechanical torsional resonator with unprecedented torque sensitivity of 2.9 yNm/√Hz.